2001
DOI: 10.1002/jbm.1252
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of primary and immortalized cell adhesion characteristics to modified polymer surfaces: Toward the goal of effective re‐epithelialization

Abstract: Facilitating tissue regeneration or replacement requires development of synthetic surfaces that promote cell adhesion, migration, and proliferation. Two successful approaches have been to incorporate minimal cell adhesion recognition sequences at the biomaterial surface and to integrate the entire adhesion molecule into a compatible synthetic matrix. While adhesion assays using immortalized cell lines are important in evaluating synthetic materials, cell type and source play a significant role in the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
9
1
1
Order By: Relevance
“…The cell type and its origin also become important aspects to take into account in a biocompatibility study. These results underline the need of using both established cell lines and primary cells to assess polymer biocompatibility 18,19…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The cell type and its origin also become important aspects to take into account in a biocompatibility study. These results underline the need of using both established cell lines and primary cells to assess polymer biocompatibility 18,19…”
Section: Resultsmentioning
confidence: 62%
“…Although our preliminary studies have demonstrated a good biocompatibility of PCL with the established cell line L929 of fibroblasts,10 further studies with primary cells are necessary to assess it. As it is well known, there could be some differences in cell behavior between an established cell line and cells harvested directly from tissue even being the same cell type 18,19…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, the tightly controlled degradation of the extracellular matrix is a key process that is mainly dependent on the activity of matrix metalloproteinases (MMPs) and the tissue inhibitors of MMP (TIMP). MMPs are capable of [74][75][76][77], the surface roughness was shown to have an significant influence on cell adhesion, proliferation and differentiation, as well as on the kinetics of appearance and activity levels of MMP and TIMP on primary rat cells of the upper aerodigestive tract (oral, pharyngeal and esophageal origin). The rough modification of the SMP surface supported the cell growth dependent on the cell type and the time of cell growth, rather than the smooth surface modification.…”
Section: Sterilization and In Vitro Cytotoxicity Testingmentioning
confidence: 99%
“…The highest MMP-1 and MMP-2 levels corresponded with the highest TIMP levels, and vice versa. These results were supposed to be affected by different mechanical loading by the surface roughness, and besides the chemical composition of the material surface, also by the resulting surface properties, often expressed in terms of hydrophobicity, that are the main predictors of protein adsorption and, thus, cell adhesion [77][78][79].…”
Section: Sterilization and In Vitro Cytotoxicity Testingmentioning
confidence: 99%
“…Die Topographie der Oberfläche, an die Zellen anheften, spielt eine große Rolle in der Regulation des Zellverhaltens [17]. Bisher ist jedoch sehr wenig bekannt über den Einfluss der Oberflächenstruktur von polymeren Biomaterialien auf die Synthese von Enzymen, die direkt in das Remodeling der Extrazellulärmatrix auf der zellbesiedelten Oberfläche von Polymeren involviert sind.…”
unclassified